ESTIMATE OF GENETIC PARAMETERS AND SOME NON-GENETIC FACTORS TO PRODUCE MILK AND ITS COMPONENTS IN THE LOCAL AND SHAMI GOATS CENTERAL IRAQ - Jassim, Saleh Hassan; Khalil, Zainab Sami (Diyala Agricultural Sciences Journal, 2018)
This study was conducted on 200 goat which 120 goat Cypriot and 80 local goat, a breed for August 18 Shami, 12 local father in ruminant research station in Abu Ghraib belong to General Board of Agricultural Research, to estimate genetic parameters (heritability, genetic links, genetic and phenotypic value) and some of the factors is non genetic recipes for milk production and its components under Iraqi environmental conditions, use the general linear model method (GLM-General linear model) within SAS program in the statistical analysis of the data. The results of the current study showed that the value of the equivalent genetic recipe total milk production of 0.45- counter fat 0.22 ratio while the equivalent genetic recipe protein ratio of 0.34, whereas the genetic correlations were estimated and the phenotypic traits studied. The genetic value of the link between the total milk production and the percentage of fat was a non significant and negative - 0.24. The genetic correlation between the value of the total milk production and protein content was negative and low -0.15 while the genetic link between the components (between fat content and protein) positive and highly significant 0.73. The phenotypic correlation, amounting to phenotypic value of the link between the status of the total milk production and the percentage of fat and protein 0.14- and 0.16- was negative and low values while the high correlation phenotypic between fat content and protein 0.65. Hertiability values of the goats for a recipe total milk production between 95. 12. 110.75, hertiability values of the ratio of fat ranged from 1.812- and 0.109 while the protein content ranged between 0.691- and 0.0851-. The results also showed that the fixed factors studied had a significant effect on total milk production, except for the type of birth and sex of the kids had no effect on milk production as well as there was not any effect of the month and the type of birth and the presence of horns on the ratios of fat and protein.